Evaluation of Sports Coaching Programs in Indonesian Using the Countenance Model - Triatmo Joko Purnomo; Wawan Eko Prasetyo; Mochammad Nasmay Lupita; Shokhan Abdulrahman (CV. FOUNDAE, 2024)
Various kinds of research aimed at evaluating the field of sports using the countenance model have been carried out. This literature review uses a countenance evaluation model to examine the condition of the coaching program in sports in Indonesia. The method used is the Google Scholar database on sports evaluation of the countenance model. Sources of data used were primary data from 15 articles, with the type of evaluation research. The article selection stage was carried out by (1) Identification, (2) screening, (3) eligibility, and (4) being included in the criteria. From the results of the article study, the coaching program in each sport was poor. The most prominent thing is at the transaction stage. There were many shortcomings, from inadequate facilities, the consumption of athletes that did not meet nutritional standards, and the lack of athlete welfare.